Perspectives on knowledge management capabilities in universities: A qualitative identification of organisational factors - ÇETİN, MÜNEVVER (My University, 2022)
Prior research has had a limited approach to identifying organisational factors related to knowledge management (KM) practices of higher education institutions (HEIs), the centre for knowledge creation. This qualitative study explored such factors affecting KM capabilities from the perspectives of 30 full-timeacademics in public universities, and identified the dimensions of the KM capabilities framework. Results revealed that physical conditions, budget, human and technological resource management, division of labour, workload, time management, communication, bureaucracy, structural differentiation, motivation, individualism, and organisational behaviour affect KM infrastructure capabilities; bureaucracy, KM teams, institutional platforms, organisational structure, knowledge maps, vision, individual attitudes, academic collaboration, process management, budget, decision-making processes, sustainable academic KM, transparency, labour force, knowledge security, organisational culture, accessibility, and archiving affect KM process capabilities. These results contribute to identifying the organisational factors influencing KM that are critical to guiding practitioners and administrators of HEIs in developing more effective KM strategies and practices.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities